Postoperative C-Reactive Protein as a Predictor of Postoperative Pancreatic Fistula after Pancreaticoduodenectomy - Khadka, Namrata; Maharjan, Narendra; Bhandari, Ramesh Singh; Lakhey, Paleswan Joshi (Journal of Institute of Medicine Nepal, 2025)
Introduction Postoperative pancreatic fistula (POPF) has adverse effects on the outcomes of patients after Pancreaticoduodenectomy PD. Thus, an accurate predictor of POPF is essential. This study aimed to identify C-Reactive Protein (CRP) on the first postoperative day (POD1) as a predictor of clinically relevant postoperative pancreatic fistula (CR-POPF). Methods It was a prospective observational study performed at Tribhuvan University Teaching Hospital, Nepal, from March 2019 to November 2019. Forty-nine patients who underwent PD were enrolled in the study. Demography, clinicopathological characteristics, postoperative complications, and CRP on POD1 were recorded. Statistical analyses were performed to identify the association of POD1 CRP with CR-POPF. Results The mean age was 56.94 ± 10.10 years, with a nearly equal gender distribution. Clinically relevant postoperative pancreatic fistula (CR-POPF) occurred in 13 patients (26.5%). Patients with CR-POPF had higher mean postoperative day 1 serum C-reactive protein (CRP) levels (123.84 ± 42.90 mg/L) compared to those without CR-POPF (93.35 ± 67.02 mg/L); however, the difference was not statistically significant (p = 0.134). No significant associations were found between CR-POPF and preoperative or intraoperative variables, including pancreatic duct diameter, gland texture, and operative time. Conclusion Although serum CRP levels on postoperative day 1 were higher in patients who developed clinically relevant POPF, the difference was not statistically significant in this study. Therefore, CRP alone may not be a reliable early predictor of CR-POPF.